Functional planning units for the management of an endangered Brazilian titi monkey. Issue 5 (19th January 2017) - Gouveia, Sidney F.; Souza‐Alves, João Pedro; de Souza, Bruno B.; Beltrão‐Mendes, Raone; Jerusalinsky, Leandro; Ferrari, Stephen F.
Abstract : Conservation practices in the tropics often rely on the data available for a few, better‐known species and the adoption of an appropriate spatial scale. By defining a set of landscape units that account for critical aspects of the focal species, the information available on these conservation targets can support regional conservation policies. Here, we define and classify adjacent landscapes, termed planning units, to orientate management decisions within and among these landscapes, which are occupied by an endangered flagship primate species (Coimbra‐Filho's titi monkey, Callicebus coimbrai ) from eastern Brazil. We use landscape boundaries (highways and river systems), and a high‐resolution map of forest remnants to identify continuous and manageable landscapes. We employed functional landscape metrics based on the species' dispersal ability and home range size to characterize and classify these landscapes. We classified planning units by scoring them according to a suite of selected metrics through a Principal Component Analysis. We propose 31 planning units, containing one to six C. coimbrai populations, most with low values of habitat availability, functional connectivity and carrying capacity, and a high degree of degradation. Due to this poor landscape configuration, basic management practices are recommendable. However, additional aspects of the landscapes and the populations they contain (e.g., matrix type and genetic variability) should improve the scheme, which will require a closer integration of research aims with socio‐political strategies. Even so, our scheme should prove useful for the combination of information on conservation targets (i.e., focal species) with management strategies on an administrative scale. Abstract : We propose a scheme to define and classify planning units across landscapes to guide management practices for a Brazilian titi, Callicebus coimbrai . The scheme is reproducible for other species and locations, according to their specific requirements.